2020
DOI: 10.1111/cid.12953
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of the influence of prosthodontic factors on peri‐implant bleeding index and marginal bone level in a molar site: A cross‐sectional study

Abstract: Background: Peri-implant tissue condition can result from prosthodontic, surgical and bacteriological factors. Purpose: This study investigated the effects of prosthodontic factors on peri-implant tissue. Materials and Methods: Subjects were 140 patients with 310 implants from Osaka University Dental Hospital. Prosthodontic factors examined were the connection type, the suprastructure retention type, the material of the abutment and the mesiodistal and buccolingual prosthetic form of the superstructure as emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…The aim was to identify if a >30° EA might influence interproximal bone loss. The present findings partially agree with other recently published papers; a multivariate analysis to investigate the influence of prosthetic factors on the marginal bone level was conducted by Inoue et al [ 15 ]. It was stated that there is no statistically significant correlation between the emergence angle and marginal bone level.…”
Section: Discussionsupporting
confidence: 94%
“…The aim was to identify if a >30° EA might influence interproximal bone loss. The present findings partially agree with other recently published papers; a multivariate analysis to investigate the influence of prosthetic factors on the marginal bone level was conducted by Inoue et al [ 15 ]. It was stated that there is no statistically significant correlation between the emergence angle and marginal bone level.…”
Section: Discussionsupporting
confidence: 94%
“…In the mentioned 6 months follow-up study, the authors found that the modification of the restorative contour in the test group-to facilitate the oral hygiene-resulted in significant better clinical outcomes than the control group, in which the restorative contour was not modified (de Tapia et al, 2019). Consistently, outcomes from a cross-sectional study showed a tendency (p > .05) towards inferior BOP levels at implants with a restorative angle between 20° and 40° (Inoue et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…Despite the wide use of these restorations in clinical practice, evidence regarding the clinical and biological outcomes is still lacking. This lack of information is of particular importance as recent studies revealed that the restorative or prosthetic design may influence biological outcomes such as marginal bone loss (Inoue et al, 2020; Katafuchi, Weinstein, Leroux, Chen, & Daubert, 2018; Majzoub, Chen, Saleh, Askar, & Wang, 2021; Yi, Koo, Schwarz, Ben Amara, & Heo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The three eligible studies, Katafuchi et al (2018), Yi et al (2020), and Inoue et al (2020), had a retrospective case‐control and cross‐sectional design, respectively. The study by Katafuchi et al (2018) collected data from patients who had implants placed in a university setting (Washington) during the period of 1998 to 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Yi et al (2020) collected data from patients who had implant restorations placed between March 2002 and February 2012 at Seoul National University Dental Hospital. Inoue et al (2020) described patients who received implant treatment in the molar region at the Department of Fixed Prosthodontics, Osaka University Dental Hospital, and who visited for maintenance from May 2013 to August 2018.…”
Section: Resultsmentioning
confidence: 99%